2023
DOI: 10.3390/nu15051234
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation and Clinical Outcomes in Severe COVID-19 Patients—Randomized Controlled Trial

Abstract: COVID-19 symptoms vary from asymptomatic cases to moderate and severe illness with patients needing hospitalization and intensive care treatment. Vitamin D is associated with severity of viral infections and has an immune-modulatory effect in immune response. Observational studies showed a negative association of low vitamin D levels and COVID-19 severity and mortality outcomes. In this study, we aimed to determine whether daily supplementation of vitamin D during intensive care unit (ICU) stay in COVID-19 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…However, Domazet Bugarin et al. acknowledged that one of the main limitations of that study was the small sample size [ 10 ]. Initially, they wanted to recruit at least 274 patients to be able to detect a two-day difference in the primary outcome.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Domazet Bugarin et al. acknowledged that one of the main limitations of that study was the small sample size [ 10 ]. Initially, they wanted to recruit at least 274 patients to be able to detect a two-day difference in the primary outcome.…”
Section: Reviewmentioning
confidence: 99%
“…Initially, they wanted to recruit at least 274 patients to be able to detect a two-day difference in the primary outcome. Therefore, they suggest the available results would serve for larger and more powerful studies in the future [ 10 ]. The other study by Brunvoll et al also reported that there was no difference when using 400 IUs of VD daily for six months [ 11 ].…”
Section: Reviewmentioning
confidence: 99%
“…), that true deficiency is likely to worsen infectious outcomes, including those from COVID, and that vitamin D is essential for a variety of normal immunological functions. Why, therefore, save maybe in individuals with the absolute lowest levels, do all the randomized studies conducted yet fall short of the lofty expectations that vitamin D treatment will prevent or alleviate COVID-19 [ 30 ]? According to what I understand, a deficiency state happens when a substance is deficient, and this deficiency results in a pathological condition that can be treated or avoided by replacing or supplementing the missing substance.…”
Section: Reviewmentioning
confidence: 99%
“…There is no deficient state when there is a low calcium level, low albumin level, and systemic inflammation. Patients with low vitamin D levels should not be deemed to have a deficiency if supplementation is offered to them and results are not improved [ 30 ]. In our eagerness to show how important nutrition is, we frequently overlook this kind of connection between nutrients and the severity of a disease.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation